Synthesis and Structural Characterization of Lithium-Based Metal-Organic Frameworks - Banerjee, Debasis; Borkowski, Lauren A.; Kim, Sun Jin; Parise, John B. (American Chemical Society, 2009)
Two lithium-based metal-organic frameworks, Li-2(C14H8O4) [Li-2(4,4'-BPDC) [1]; ULMOF-2, UL = ultralight; BPDC = biphenyldicarboxylate]; space group P2(1)/c, a = 12.758(2) angstrom, b = 5.142(4) angstrom, c = 8.00(2) angstrom, beta = 97.23 degrees, V = 520.6(14) angstrom(3) and Li-2(C14H8O6S) [Li-2(4,4'-SDB) [2]; ULMOF-3, UL = ultralight; SDB = sulfonyldibenzoate], space group P2(1)/n, a = 5.5480(11) angstrom, b = 23.450(5) angstrom, c = 10.320(2) angstrom, beta = 96.47(3)degrees, V = 1334.1(5) angstrom(3), were synthesized. Compounds I and 2 were synthesized by solvothermal methods and were characterized using single crystal X-ray diffraction. Structure 1 consists of layers of two-dimensional antifluorite related LiO motif connected by BPDC linkers, whereas structure 2 is constructed by a combination of tetrameric lithium polyhedral clusters connected by the sulfonyldibenzoate linker. The frameworks are stable up to 575 and 500 degrees C, respectively, under N-2 atmosphere.
Keywords: HYDROGEN STORAGE MATERIALS; COORDINATION POLYMER; GAS-ADSORPTION; CARBON-DIOXIDE; PORE-SIZE; SORPTION; TEMPERATURE; CATALYSIS; CAPACITY; LIGANDS